Renegades New Year - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows three partially clothed men. The man on the left appears to be wearing a dark colored diaper and has a store bought netted Christmas stocking filled with gifts hanging around his neck. The man in the middle wears a jockstrap and a similar Christmas stocking around his neck. The man on the right appears to be wearing a skirt and has a oversized baby bottle in his hand.